Redistributing Income under Proportional Representation: A Correction - Morelli, Massimo; Negri, Margherita (Journal of Political Economy, 2019)
Austen-Smith (2000) reports a theoretical result that if the cost of entering the workforce is suﬃciently low, winner-take-all political systems induce endogenous redistribution levels that are systematically lower than those determined by proportional representation systems (Proposition 6). The proof in Austen-Smith (2000) has a mistake. We explain the mistake and oﬀer an alternative proof. The conclusion of the original paper continues to hold.